Riparian Reserves Promote Insectivorous Bat Activity in Oil Palm Dominated Landscapes - Mullin, Katherine E.; Yoh, Natalie; Mitchell, Simon L.; Basrur, Saloni; Seaman, Dave J. I.; Bernard, Henry; Struebig, Matthew J. (Frontiers in Forests and Global Change, 2020)
The expansion of oil palm agriculture has contributed to biodiversity loss in Southeast Asia and elsewhere in the tropics. Riparian reserves (areas of native forest along waterways) have the potential to maintain forest biodiversity and associated ecological processes within these agricultural landscapes. Using acoustic sampling, we investigated the value of riparian reserves for insectivorous bats in oil palm plantations in Sabah, Malaysian Borneo. We compared general bat activity, foraging activity, and species occupancy between riparian areas in forest and riparian reserves in oil palm plantations. Overall bat activity varied little between riparian reserves in oil palm and riparian forest. Rather, activity was greatest in areas with a high forest canopy, irrespective of how much forest was available within or outside the riparian reserve. Bat foraging activity, as well as the occupancy of two species, was greatest in the forest sites, and while bats were detected in the oil palm riparian reserves, both foraging and occupancy were more associated with topographic ruggedness than forest amount or height. Our results indicate that habitat structure within riparian reserves may be more important than reserve size for supporting insectivorous bat diversity within oil palm landscapes. These findings provide important insights into the extent of the ecological benefits provided by conservation set-asides in forest-agricultural landscapes in the tropics.